Investigating Students' Perspectives on Implementation of 3C3R PBL on Climate Change Topic Using the Rasch Model - Anggie Siti Perdani; Siti Eneng Sururiyatul Mu’aziyah; Yunita Miftahul Jannah (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2025)
This study investigates high school students' responses to the implementation of the 3C3R Problem-Based Learning (PBL) model in climate change education. Given the complexity of climate issues, the 3C3R model, emphasizing Content, Context, Connection, Research, Reasoning, and Reflection, was applied to foster students' critical thinking and collaborative problem-solving. A descriptive quantitative method was used, with data collected through questionnaires and analyzed using the Rasch model. The Wright Map was employed to visualize the distribution of student agreement. Findings show that students responded positively to structured materials, meaningful group tasks, and opportunities to present their work. The most endorsed items highlighted teacher preparation, honest self-assessment, and active involvement in poster presentations. However, student responses also indicated limited participation in collaborative aspects like experiment design and shared responsibility during group work. These results suggest that while the 3C3R PBL model enhances cognitive and emotional engagement, additional support is needed to improve students' communication and teamwork. The study offers valuable insights for educators aiming to deepen student involvement in climate change learning